The physicochemical characterisation of cyclodextrin inclusion compounds with non-steroidal anti-inflammatory drugs - Brown, Gavin Robert (Department of Chemistry, 2017)
The cyclodextrins and their derivatives have been utilised as complexing agents for a wide range of pharmaceutical compounds, through their ability to include small molecular weight molecules inside an annular cavity formed by linked glucose residues of varying number. The non-steroidal anti-inflammatory drugs (NSAIDs), a group of agents that share a similar therapeutic effect in the management of inflammatory processes in the body, have been studied as guest molecules for inclusion in cyclodextrins, due to a number of potential advantages that are conferred by complexation, such as improved bioavailability, modified side-effect profiles and the control of drug release from novel formulations. This study has tested a number of commonly used NSAIDs belonging to certain structural groups, together with a number of cyclodextrins and their derivatives, and attempts have been made to prepare complexes in the solid state and characterise them using physicochemical methods. The cyclodextrins used were native seven' and eight-membered β- and y-cyclodextrin and two methylated derivatives of β-cyclodextrin, namely heptakis(2,6-di-0-methyl)-β-cyclodextrin and heptakis(2,3,6- tri-O-methyl)-β-cyclodextrin, abbreviated as DIMES and TRIMEB respectively. NSAIDs belonging to the salicylate, fenamate, profen, oxicam and indene structural groups were used. These included diflunisal, mefenamic acid, niflumic acid, tolfenamic acid, flufenamic acid, ibuprofen, ketoprofen, piroxicam, tenoxicam, indomethacin and sulindac.